The Demographic Challenge Analyzed Through Ageing Indices in Extremadura and Andalusia (Spain) with Cluster Mapping Tools - José-Manuel Sánchez-Martín; José-Luis Gurría-Gascón; Juan-Ignacio Rengifo-Gallego (Land)
This study examines the demographic dynamics of Extremadura and Andalusia, two autonomous communities in southern Spain characterized by low income levels and marked territorial differences in terms of ageing and depopulation. Based on the observation of growing demographic pressure associated with low birth rates and emigration to more economically dynamic areas, a methodological approach based on spatial analysis techniques is proposed. In particular, the ageing index and demographic dependency ratio indicators are used, applying tools such as Hot Spot Analysis and Cluster and Outlier Analysis to identify significant spatial patterns and outliers. The results show a high concentration of ageing and dependency in provinces such as Cáceres and Almería, suggesting greater demographic vulnerability. In contrast, urban areas such as Seville and Granada, as well as the Guadalquivir depression, show more favorable indicators, reflecting greater resilience. Likewise, municipalities with demographic behavior that is anomalous with respect to their surroundings are detected, which raises the need for micro-territorial studies aimed at understanding these exceptions and designing more effective public policies adapted to the local context.